Invitro cytotoxic activity of Baliospermum Montanum leaves on cervical cancer- Hela cell lines and chemical characterization by GCMS - SEETHALAXMI RADHAKRISHNA; DR. P. SARAVANA KUMARI (International Journal of Pharma and Bio Sciences, 2018)
Cervical cancer is the second most common cancer among women worldwide and represents a major concern for public health. Medicinal Plants are the abundant sources of phytochemicals used in pharmaceutical industries for cancer therapy throughout the world. Baliospermum montanum an endangered medicinal plant belongs to family Euphorbiaceae. The present study was carried out to evaluate the anticarcinogenic activity of methanol extract of Baliospermum montanum leaf against HeLa cell lines for cervical cancer and analysed for the phytochemical constituents. The anticarcinogenic activity on HeLa cell lines was measured by MTT assay. Identification of the chemical constituents was carried out using Gas Chromatography-Mass Spectroscopy [GCMS]. Methanol extract showed a significant amount of cytotoxicity in HeLa cell lines with IC value 255µg/ml. GC MS analysis confirmed the presence of 14 compounds where topotecan was found to be the major compound. The present study indicates that the plant possesses various phytochemicals having anticancer and cytotoxic properties. The study confirms that Baliospermum montanum has the potential to be a good source for cancer therapy.